Thermally Stable Multilamellar Structure of DNA/Cationic Lipid Complex in the Bulk State - Wu, Ching-Mao; Lin, Szu-Yin (Journal of Applied Solution Chemistry and Modeling, 2014)
The effect of temperature on the two types of multilamellar structures, LI and LII, formed by the complexes of DNA with a cationic lipid, cholesteryl 3β-N-(dimethylamionethyl) carbamate (DC-Chol), in the bulk state has been investigated by small angle X-ray scattering (SAXS). LI phase composing of A-DNA intercalated between the lipid bilayers with tilted tails was formed at lower lipid-to-base pair molar ratio (x < 2), while LII phase consisting of B-DNA bound to untilted lipid was formed at x > 2. In addition to the differences in lipid packing state and DNA conformation, these two lamellar phases also displayed different thermal stability. LI phase was highly thermally stable as its interlamellar distance remained essentially unperturbed even after the denaturation of A-DNA in the complex at elevated temperature. By contrast, the interlamellar distance of LII phase decreased with increasing temperature due to the release of bound water and B-DNA denaturation.